A qualitative insight into the perceptions and COVID-19 vaccine hesitancy among Pakistani pharmacists. Issue 1 (31st January 2022) - Yaseen, Muhammad Osama; Saif, Arifa; Khan, Tahir Mehmood; Yaseen, Misha; Saif, Alia; Bukhsh, Allah; Shahid, Muhammad Nabeel; Alsenani, Faisal; Tahir, Humera; Ming, Long Chiau; Amin, Muhammad Usman; Suleiman, Amal K.; et al.
ABSTRACT: A qualitative exploration of pharmacists' perceptions regarding COVID-19 conspiracies and their willingness to get vaccinated. A semi-structured questionnaire guide was developed using ground theory to conduct in-depth interviews. A total of 36 participants gave consent for an audio-recorded interview. Results have shown that most of the respondents believed that SARS-CoV-2 is a natural virus, not man-made, that causes a disease just like other viruses and it is absurd to believe that the vaccine is being used by foreign powers for the implantation of microchips just to control humans. A general opinion thatwhich reflected from the in-depth interview is that the pharmaceutical companies may be hiding some important information on COVID-19 to promote the sale of their product. Some doubts on the reliability and trustworthiness on the COVID-19 vaccine safety and efficacy data were noticed among the respondents. Factors leading to COVID-19 vaccine hesitancy were adverse reaction, cost of COVID-19 vaccine, and limited data on safety and efficacy profile of COVID-19 vaccine. COVID-19 vaccine hesitancy among health professionals is a major hindrance to our current fight against COVID-19 pandemic. Findings of this study are alarming, and the stakeholders must consider this ongoing vaccination campaign as an opportunity to formulate a mechanism to ensure high vaccination rate among general public and healthcare providers in Pakistan. KEY POINTS What was already known? According to World Health Organization (WHO), vaccine hesitancy is one of the ten major threats to global healthcare system and it is a major barrier to achieve herd immunity around the globe. Pakistan has begun vaccinating its people in a systematic phase-wise manner under which the healthcare workers and elderly people are prioritized for vaccination. Previous experience tells us that vaccine hesitancy is a major problem in Pakistan and it is better to understand perceptions of pharmacists about COVID-19 vaccine who are the primary source of information for most of general population. What this study adds: This study is first of its kind to explore vaccine hesitancy among Pakistani pharmacists and the results of this study show that majority of the participants were willing to get COVID-19 vaccine and few of them have even got themselves vaccinated at the start of vaccination campaign. Many among the willing participants considered cost of vaccine, adverse reactions, limited data, safety, and efficacy as major hindrance to their decision to get vaccine. Few participants were found highly vaccine-hesitant because of their staunch belief in the prevalent myths and rumors about COVID-19 vaccine.